(untitled) (Philology, 2026)
The paper delineates the conceptual framework of the notion “specialised language”. The authors present the approach chosen by them to delimit a substantive academic discipline, which is to study the phenomenon of “specialised language” in all its aspects as well as the possible directions of its further development. The authors’ conception is set out as a theory of specialised language, trying to interconnect a multitude of viewpoints and approaches to the subject discussed. Based on some existing definitions, models and overall perceptions about the nature of specialised language, the paper presents traits and issues of the scientific field which studies and examines it. The key theses of this research are based on the notion that language and culture are interrelated. The process of emergence and development of the conception of “specialised language” is also traced in the context of diverse theories interwoven in its construction. Particular emphasis is placed on the interrelation between “specialised” and “foreign” language in the contemporary world. Starting from the fundamental approach, the paper also places a new focal point on the role this scientific field plays in modern linguistics in the light of the opportunities it presents for posing further linguistic issues for research. The paper contributes in this regard by both outlining arguments about the necessity of a dedicated and thorough cultivation of the discipline “specialised language linguistics”, and by giving an impetus to seeking ways, means and techniques in FLT for specific purposes in university education and vocational training in order to place it on a more pragmatic axis.